Inventory Of Local Plant Species With Potential As Botanical Pesticides In Karo Regency, North Sumatra, Indonesia: Inventarisasi Tumbuhan Lokal Berpotensi Sebagai Pestisida Nabati Di Kabupaten Karo, Sumatera Utara - Riki Kurniawan; Maman Suryaman; Suhardjadinata (Nabatia, 2026)
The increasing use of synthetic pesticides in intensive agricultural systems has caused various adverse impacts, including pest resistance, environmental contamination, and pesticide residues in agricultural products. Botanical pesticides derived from local plant resources represent an environmentally friendly alternative for sustainable pest management. This study aimed to inventory and botanically identify local plant species with potential as botanical pesticides in Karo Regency, North Sumatra, Indonesia. The research was conducted from April 2026 to Juny 2026in Kebayaken, Kubucolia, and Semangat Villages using an exploratory survey approach. Plant samples were collected based on information obtained from local communities, followed by specimen collection, morphological documentation, and botanical identification using morphological characteristics and taxonomic references. The collected data were analyzed descriptively based on species richness, family composition, growth habit, plant parts utilized, and target pest organisms. The results revealed 16 plant species belonging to eight families, with Zingiberaceae and Asteraceae being the dominant families. Herbaceous plants constituted the predominant growth habit, while leaves and rhizomes were the most frequently utilized plant parts for botanical pesticide preparation. This inventory provides baseline scientific information on the diversity of local plant species with potential as botanical pesticides in Karo Regency and serves as a valuable foundation for future studies on secondary metabolite characterization, bioactivity evaluation, and the development of botanical pesticides derived from local biological resources to support sustainable agriculture.